Problem Solving Ability Viewed From The Adversity Quotient on Mathematics Connected Mathematics Project Learning (Cmp) With Etnomathematics Nuanced - Suryapuspitarini, Betha Kurnia; Nino Adhi, Nuriana Rachmani Dewi (Unnes Journal of Mathematics Education Research, 2018)
This study has purpose to (1) determine the effectiveness of learning by using Connected Mathematics Project with ethnomathematics nuanced to enhance the problem solving ability (2) to find out the increase of love local culture characters of students in the learning of Connected Mathematics Project, and (3) to describe the problem solving ability of students vied from the adversity quotient. This research applied mixed method research type with sequential explanatory design. Subjects in this study was determined by the score of the adversity quotient by using the Adversity Response Profile to the students of grade VIIA of SMP N 12 Semarang. Data collection techniques was done by using observation, test and interview. The effectiveness was analyzed based on (1) test of average similarity; (2) test of completeness, (3) test of proportion , (4) test of average different test. The increased of love local culture character wa analyzed by using paired sample t test. The results of the study showed that the learning model of Connected Mathematics Project with ethnomathematics nuanced is effective toward the problem solving ability. Students with Climber category tend to have a better problem solving abilities than students with Quitter category and Camper. Students wuth Quitter category can understand problem, but less able to plan a problem solving and complete the problem solving plan and not being able to crosscheck the problem solving. Students with Camper category can understand problems and devise a plan for the problem solving, but less able to carry out the problem solving plan and crosscheck the problem solving. Students with Climber category were able to understand a problem, plan the problem solving and implement the problem solving plan, as well as re-examine the problem solving obtained properly.